2020
DOI: 10.1007/s00408-020-00335-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Transcutaneous Electrical Nerve Stimulation on Pain, Pulmonary Function, and Respiratory Muscle Strength After Posterolateral Thoracotomy: A Randomized Controlled Trial

Abstract: Purpose To evaluate the effects of transcutaneous electrical nerve stimulation (TENS) compared to placebo TENS and a control group on pain, pulmonary function, respiratory muscle strength, and analgesic medications in the postoperative period of thoracotomy in an Intensive care unit (ICU). Methods Patients who had undergone posterolateral thoracotomy were randomly allocated to receive TENS during ICU stay, or placebo TENS, or into the control group. All groups received conventional physiotherapy. We analysed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…However, some studies demonstrate the effects of TENS on other orthopedic trauma surgeries 4,9,10,[12][13][14][15] . Moreover, many studies address the effects of TENS on other types of surgery 8,11,[16][17][18][19][20][21][22][23] The results showed that almost continuous stimulation by high-frequency TENS associated with a predefined exercise and mobilization protocol during the first phase of ACL reconstruction rehabilitation led to a significant additional effect in improving acute postoperative pain. Forogh et al 3 added TENS to the immediate postoperative protocol in 70 athletes who underwent ACL reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies demonstrate the effects of TENS on other orthopedic trauma surgeries 4,9,10,[12][13][14][15] . Moreover, many studies address the effects of TENS on other types of surgery 8,11,[16][17][18][19][20][21][22][23] The results showed that almost continuous stimulation by high-frequency TENS associated with a predefined exercise and mobilization protocol during the first phase of ACL reconstruction rehabilitation led to a significant additional effect in improving acute postoperative pain. Forogh et al 3 added TENS to the immediate postoperative protocol in 70 athletes who underwent ACL reconstruction surgery.…”
Section: Discussionmentioning
confidence: 99%
“…These findings corroborate previous studies that analyzed analgesic intake with TENS application after several types of surgeries. Some authors addressed the use of opioids after thoracic surgery and showed a lower intake for patients receiving TENS compared to the control group 21 . Silva et al 10 showed that continuous TENS application for 72 after proximal femoral fracture surgery significantly decreases drug intake.…”
Section: Discussionmentioning
confidence: 99%
“…TENS can also be used as an adjuvant therapy after surgery. Hush et al [90] show that after thoracotomy in the intensive care unit (ICU), TENS adjuvant therapy can relieve pain in the first 12 h. As one of the difficult to treat diseases, eye pain usually cannot be relieved because of the difficulty of treating the ocular surface. In a recent TNES assisted long-term treatment of eye pain, the TENS experimental group reduced pain by 27.4% compared to the control group, which can assist in the treatment of eye pain [91].…”
Section: Electrical Nerve Stimulation For Analgesicmentioning
confidence: 99%
“…A study analyzed the use of opioids after thoracic surgery and demonstrated a lower opioid intake for patients receiving TENS in comparison to the control group. (11). Silva et al (15) demonstrated that continuous use of TENS (24 hours a day, ending 72 hours after surgery) for proximal femoral fracture significantly decreased drug intake (15).…”
Section: Tens In the Acl Postoperative Periodmentioning
confidence: 99%
“…In comparison to other analgesic methods, it also has the advantage of minor side effects (10). Due to this analgesic effect, TENS can be administered in the postoperative routine of several surgical conditions as an adjunct to conventional opioid analgesia (11). This study evaluates the effects of using high frequency TENS on pain, function, and opioid analgesic consumption in the immediate postoperative period of ACL reconstruction.…”
Section: Introductionmentioning
confidence: 99%